2008
DOI: 10.1111/j.1529-8817.2008.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

TRANSPORT AND DEFENSIVE ROLE OF ELATOL AT THE SURFACE OF THE RED SEAWEEDLAURENCIA OBTUSA(CERAMIALES, RHODOPHYTA)1

Abstract: Natural within-thallus concentrations of elatol produced by Laurencia obtusa (Huds.) J. V. Lamour. inhibit herbivory and prevent fouling. However, elatol occurs in larger amounts within the thallus compared with the quantities from the surface of this alga. We evaluated whether the surface elatol concentrations inhibit both herbivory and fouling and whether the content of corps en cerise can be transferred to the external cell walls. Surface elatol concentrations did not inhibit herbivory by sea urchins, settl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 61 publications
1
38
0
9
Order By: Relevance
“…Hence, FalvobacteriumVibrio complex was present in a density of 42±2~64± 4 CFU cm -2 on the surface of L. majuscula. Details of total bacterial count and bacterial species composition on K. alvarezii surface during disease outbreak were reported by Vairappan and Chong 2006. The proposed defense role of halogenated metabolites in Laurencia was further substantiated with the detailed investigation of Sudatti et al (2008), which proved a transportation mechanism of halogenated metabolites from "corps en cerise" to the surface of L. obtusa. Based on these findings, it is conceivable that "ice-ice" disease bacteria and halogenated metabolites can come into contact on the surface of L. majuscula, where these compounds could function as a defense against pathogens.…”
Section: Discussionmentioning
confidence: 94%
“…Hence, FalvobacteriumVibrio complex was present in a density of 42±2~64± 4 CFU cm -2 on the surface of L. majuscula. Details of total bacterial count and bacterial species composition on K. alvarezii surface during disease outbreak were reported by Vairappan and Chong 2006. The proposed defense role of halogenated metabolites in Laurencia was further substantiated with the detailed investigation of Sudatti et al (2008), which proved a transportation mechanism of halogenated metabolites from "corps en cerise" to the surface of L. obtusa. Based on these findings, it is conceivable that "ice-ice" disease bacteria and halogenated metabolites can come into contact on the surface of L. majuscula, where these compounds could function as a defense against pathogens.…”
Section: Discussionmentioning
confidence: 94%
“…In order to develop a better understanding of chemically mediated communication on and with the alga, it is important to detect the allocation of secondary metabolites within the host tissues (Dworjanyn et al 1999, Sudatti et al 2008). For such investigations, it is essential to measure the in situ concentrations and the methods of release of putative deterrents (Krug et al 2006, Paradas et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, transport between the "corps en cerise", where elatol is probably stored, and the cell wall of L. obtusa was proposed through channel-like membranous connections that shift vesicles from the "corps en cerise" to the cell wall region. Finally, it was suggested that the natural concentration of defensive chemicals on the surface of L. obtusa is probably not absolute, but may be variable according to environmental conditions [65][66][67].…”
Section: "Corps En Cerise"mentioning
confidence: 99%